ANALISIS STUDI KELAYAKAN BISNIS DITINJAU DARI ASPEK PEMASARAN DAN ASPEK KEUANGAN PADA UMKM FRUTTY TUTTY PURWOKERTO - Indrawati, Iin Dyah; Faizal Rizky Yuttama (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
The aim of this research is to study the feasibility of the Frutty Tutty Purwokerto business from a market and marketing perspektive as well as financial aspects. Frutty Tutty is a small business that combines food and drink ideas in a culinary setting. Qualitative research is used to collect primary data through interviews with business owners. The research results show that Frutty Tutty has used effective offline and online marketing strategies. Varied products, affordable prices and strategic locations are the keys to attracting customers. From the financial aspect of the Frutty Tutty business, it is a profitable business. This research provides insight into the feasibility of MSMEs such as Frutty Tutty regarding effective marketing strategies by paying attention to exploration and increasing market share.